PENENTUAN KONFIGURASI PENGADUK PADDLE PADA PENGADUKAN TKKS DI REAKTOR HORIZONTAL - Sefa Ramadhani, Tri
This research determines the effect of paddle mixer configuration on the oil palm empty fruit bunch (OPEFB) mixing performance in a horizontal reactor for enzymatic hydrolysis process qualitatively and quantitatively. The OPEFB stirring was carried out in a 27 cm (diameter) x 51 cm (length) horizontal reactor using various paddle mixer. The controlled variable were the number of the blades, the distance between paddle blades and the blade, stirrer shaft axis orientation, and the gap length between the stirrer and the bottom of reactor. The number of paddle mixers were varied into 3, 4 and 5 pairs. The distance between the paddle stirrers were varied as far as 17.5, 15, 12.5 and 9.5 cm and the distance from the paddle stirrer to the end of the reactor were varied by 10, 8.3 and 6 cm. The blade and stirrer shaft axis orientation was varied to north south-north south and north south-west east. The gap length between the stirrer and the bottom of reactor were varied by 1.4, 1.6 and 1.9 cm. The qualitative performance of OPEFB stirring was determined by visual observation, while the quantitative performance was measured by the mass distribution of OPEFB at the end of the stirring. It was concluded that the number of paddle blades used affects the OPEFB stirring intensity, the distance between the paddle blades and the distance from paddle blade to the end of the reactor both affects the number of OPEFB that slipping through the stirrer blade, the blade and stirrer shaft axis orientation affects the spreading of OPEFB, and the gap length between the stirrer and the bottom of the reactor increase the possibility of OPEFB being stuck between the stirrer blade and the reactor wall. The best paddle mixer configuration is 5 pairs of paddle blades with 9,5 cm distance between the paddle blades and 6 cm distance from paddle blade to the end of reactor, applying north south-west east orientation with 1,6 cm gap length between the stirrer and the bottom of reactor. The results of this study could provide insight to the design of a horizontal reactor, intended for reactions involving stirring of fiber-shaped feeds such as OPEFB.